Regulatory T Cells Suppress Inflammation and Blistering in Pemphigoid Diseases - Bieber, Katja; Sun, Shijie; Witte, Mareike; Kasprick, Anika; Beltsiou, Foteini; Behnen, Martina; Laskay, Tamás; Schulze, Franziska S.; Pipi, Elena; Reichhelm, Niklas; Pagel, René; Zillikens, Detlef; et al. (Frontiers in Immunology, 2017)
Regulatory T cells (Tregs) are well known for their modulatory functions in adaptive immunity. Through regulation of T cell functions, Tregs have also been demonstrated to indirectly curb myeloid cell-driven inflammation. However, direct effects of Tregs on myeloid cell functions are insufficiently characterized, especially in the context of myeloid cell-mediated diseases, such as pemphigoid diseases (PDs). PDs are caused by autoantibodies targeting structural proteins of the skin. Autoantibody binding triggers myeloid cell activation through specific activation of Fc gamma receptors (Fc-gamma Rs), leading to skin inflammation and subepidermal blistering. Here, we used mouse models to address the potential contribution of Tregs to PD pathogenesis in vivo. Depletion of Tregs induced excessive inflammation and blistering both clinically and histologically in two different PD mouse models. Of note, in the skin of Treg-depleted mice with PD, we detected increased expression of different cytokines, including Th2-specific IL-4, IL-10, and IL-13 as well as proinflammatory Th1 cytokine IFN-gamma and the T cell chemoattractant CXCL-9. We next aimed to determine whether Tregs alter the migratory behavior of myeloid cells, dampen immune complex-induced myeloid cell activation, or both. In vitro experiments demonstrated that co-incubation of immune complex-activated myeloid cells with Tregs had no impact on the release of reactive oxygen species but downregulated ß2 integrin expression. Hence, Tregs mitigate PD by altering the migratory capabilities of myeloid cells rather than their release of reactive oxygen species. Modulating cytokine expression by administering an excess of IL-10 or blocking IFN-gamma may be used in clinical translation of these findings.